2018
DOI: 10.1111/mam.12120
|View full text |Cite
|
Sign up to set email alerts
|

Camera‐trapping provides insights into adult sex ratio variability in felids

Abstract: Adult sex ratio (ASR) plays a pivotal role in many ecological processes, such as population dynamics in time and space, extinction risk and reproductive success, but few patterns in the variability in ASR have been found across species. Due to the socio‐spatial structure and polygynous mating system found in felids, ASR is expected to be female‐biased in felids in a finite area; however, ASR is also commonly found to be either balanced or male‐biased in this taxonomic group. Therefore, investigating ecological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…Our efforts for maintaining the dataset, analyzing it and disseminating our findings 46,47 have contributed to increase the scientific knowledge for this highly distinctive and charismatic taxon. Moreover, in this study we have found strong support for the VMA law for a whole taxon of carnivore species for the first time and evidently this result calls for other assessments of the VMA at the interspecific level in other taxonomic groups, both on the spatial and temporal variance in population density, before confirming its universality on ecological systems and discussing its implications more in depth.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our efforts for maintaining the dataset, analyzing it and disseminating our findings 46,47 have contributed to increase the scientific knowledge for this highly distinctive and charismatic taxon. Moreover, in this study we have found strong support for the VMA law for a whole taxon of carnivore species for the first time and evidently this result calls for other assessments of the VMA at the interspecific level in other taxonomic groups, both on the spatial and temporal variance in population density, before confirming its universality on ecological systems and discussing its implications more in depth.…”
Section: Discussionmentioning
confidence: 99%
“…Different arguments could indeed be formulated to explain this flattening of the VMA encompassing both a lower than expected variability in small species and larger variability than expected in large species. In a more optimistic scenario, our dataset may not be representative enough of the actual variability found in population densities of small cats; a scenario which we consider realistic given the strong bias in research efforts towards large cats 46 , 47 . In the worst case scenario, we cannot exclude that population densities of small cat populations are truly depressed, hence they are not able to attain their highest predicted population densities, thereby lowering the density variation in small species and ultimately flattening the VMA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations